Marked themes as context frames in research article abstracts - Chan, Swee Heng; Ebrahimi, Seyed Foad (Penerbit Universiti Kebangsaan Malaysia, 2012)
Research article abstract (RA abstract) is an important area of investigation. This importance comes from the role that it plays in the scientific community that is used to serve different writings and reading functions and purposes. It helps writers to squeeze significant information and findings of a whole research article into a compact unit and to manage information flow to be communicated in the scientific community (Martin, 2003; Ventola, 1994). This paper attempted to investigate the discourse functions (context frames) of marked themes used in Applied Linguistics and Economics research article abstracts. Sixty research article abstracts from the two disciplines published in journals of Applied Linguistics and Oxford Economic Papers in 2010 to 2011 issues were analyzed. The results revealed a significant difference in the use of validation context frame across the two disciplines. However, there were more similarities than differences regarding use of context frames in the abstracts from the two disciplines. This is discussed in the context of general and specific genre expectations as well as textual choices exercised to give text coherence. Findings of this study also supported the proposition that one micro level feature, in the form of marked theme, as thematic function, has the potential to signal the development of macro structure and rhetorical organization in abstract writing for scientific article writing.